Zoning and the Distribution of Locational Rents: An Empirical Analysis of Harris County Texas - Jeremy Groves; Eric Helland (Claremont McKenna College, Department of Economics, 2000)
The Coase theorem presents two criteria for evaluating regulation. The first is how successful the regulation is at reaching the efficient outcome relative to private solutions. The second and less discussed criterion is how the regulation affects the distribution of wealth. Previous studies of the impact of municipal zoning have focused on Coase's first criteria: whether zoning raises land values overall. There has been less focus on distributional aspects of zoning. How does municipal zoning affect the wealth of participants in the property market? Most of the existing studies focus on the transfer of rents between those who have developed property and those with undeveloped property. This study estimates the transfer of wealth between owners of existing homes that results from the creation of a municipal zoning ordinance. We find that property best suited to residential use gains in value while property with relatively higher potential as commercial property experiences a decline in the value. Our results support the contention that zoning is distributive.
Keywords: 330